Electrode mixture, lithium ion battery, and production method for lithium ion battery

By using a specific proportion of silicon capsule crystal particles and amorphous silicon particles in the electrode mixture, combined with the formation of a high ionic conductive material layer, the problem of large expansion of silicon-based electrode active materials during charging is solved, and the stability and performance of the battery are improved.

JP2025019663APending Publication Date: 2025-02-07TOYOTA JIDOSHA KK +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023123392
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing silicon-based electrode active materials have a large expansion during charging, and it is necessary to further suppress their expansion during charging.

Method used

An electrode mixture containing silicon capsule crystal particles and amorphous silicon particles is adopted, wherein the proportion of amorphous silicon particles is controlled within a specific range to ensure high ionic conductivity to suppress uneven reactions, an electrode active material layer containing silicon capsule crystal particles and amorphous silicon particles is used, and an electrode active material layer is formed by a specific process.

Benefits of technology

It effectively suppresses the expansion of electrode materials during charging and improves the stability and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019663000001
    Figure 2025019663000001
Patent Text Reader

Abstract

To provide an electrode mixture that reduces the expansion at the time of charging, a lithium ion battery that includes the electrode mixture, and a production method for the lithium ion battery.SOLUTION: An electrode mixture in the present disclosure includes a silicon clathrate particle and an amorphous silicon particle, and satisfies the following relational expression: 0 atom%<the number of silicon atoms in the amorphous silicon particle / (the number of silicon atoms in the amorphous silicon particle+the number of silicon atoms in the silicon clathrate particle)<50 atom%. A lithium-ion battery in the present disclosure includes an electrode active material layer, and the electrode active material layer contains the electrode mixture in the present disclosure. Further, a production method for a lithium ion battery in the present disclosure includes forming an electrode active material layer, and the electrode active material layer contains the electrode mixture in the present disclosure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrode composite material, a lithium-ion battery, and a method for manufacturing a lithium-ion battery.

Background Art

[0002] In recent years, battery development has been actively carried out. For example, in the automotive industry, the development of batteries used in electric vehicles or hybrid vehicles has been advanced. Also, silicon is known as an electrode active material used in batteries, particularly lithium-ion batteries.

[0003] Silicon electrode active materials have a large theoretical capacity and are effective for increasing the energy density of batteries. On the other hand, silicon electrode active materials have a problem of large expansion during charging. In contrast, it is known that by using a silicon class rate electrode active material as the silicon electrode active material, expansion during charging can be suppressed.

[0004] For example, Patent Document 1 discloses a silicon class rate electrode active material having a crystal phase of silicon class rate type II and having a composition of Na x Si 136 (1.98 < x < 2.54).

Prior Art Documents

Patent Documents

[0005]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0006] Although the silicon class rate electrode active material can suppress expansion during charging compared to a normal silicon electrode active material, it is required to further suppress expansion during charging of the silicon class rate electrode active material.

[0007] An object of the present disclosure is to provide an electrode mixture that exhibits small expansion during charging, a lithium ion battery having such an electrode mixture, and a method for manufacturing such a lithium ion battery. [Means for solving the problem]

[0008] The present inventors have found that the above problems can be solved by the following means. <Aspect 1> An electrode composite comprising silicon clathrate particles and amorphous silicon particles, and satisfying the following relationship: 0 atom%<number of silicon atoms in the amorphous silicon particles / (number of silicon atoms in the amorphous silicon particles+number of silicon atoms in the silicon clathrate particles)<50 atom%. <Aspect 2> The electrode mixture according to embodiment 1, which satisfies the following relational formula: 0 atom%<number of silicon atoms in the amorphous silicon particles / (number of silicon atoms in the amorphous silicon particles+number of silicon atoms in the silicon clathrate particles)≦30 atom%. <Aspect 3> 3. The electrode composite of claim 1 or 2, wherein the amorphous silicon particles are porous amorphous silicon particles. <Aspect 4> An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to any one of aspects 1 to 3. Lithium-ion battery. <Aspect 5> forming an electrode active material layer; and The electrode active material layer contains the electrode mixture according to any one of aspects 1 to 3. How lithium-ion batteries are manufactured. <Aspect 6> The method of embodiment 5, comprising forming the electrode active material layer by a method comprising the steps of: Providing an electrode mixture slurry containing the electrode mixture and a dispersion medium according to any one of aspects 1 to 3; and The electrode mixture slurry is applied to a substrate, and the dispersion medium is then dried to form the electrode active material layer. Effect of the Invention

[0009] According to the present disclosure, it is possible to provide an electrode mixture that expands little during charging, a lithium ion battery having such an electrode mixture, and a method for manufacturing such a lithium ion battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] 《Electrode composite material》 The electrode mixture of the present disclosure includes silicon clathrate particles and amorphous silicon particles, and satisfies the following relationship: 0atom%<number of silicon atoms in an amorphous silicon particle / (number of silicon atoms in an amorphous silicon particle + number of silicon atoms in a silicon clathrate particle)<50atom%.

[0012] Silicon clathrate particles have a small change in expansion rate due to charging and discharging, but are highly sensitive to reaction unevenness, and the expansion rate increases as the reaction unevenness progresses. In this regard, the present inventors believe that the low ionic conductivity of silicon clathrate particles is the cause of this reaction unevenness. Specifically, without intending to be bound by any theory, it is believed that the reaction is concentrated on the particle surface due to the low ionic conductivity of silicon clathrate particles, which causes the reaction unevenness to progress.

[0013] In response to this, the present inventors have discovered that by making the negative electrode composite material contain silicon clathrate particles and amorphous silicon particles with high ionic conductivity, it is possible to prevent uneven reaction from progressing within the negative electrode composite material, thereby suppressing an increase in the expansion rate.

[0014] In the present disclosure, the term "electrode mixture" refers to a composition that can constitute an electrode active material layer as it is or by further containing other components. In the present disclosure, the term "electrode mixture slurry" refers to a slurry that contains a dispersion medium in addition to the "electrode mixture" and can be applied and dried to form an electrode active material layer.

[0015] In addition, with respect to the present disclosure, the "electrode active material" can be used as either a "positive electrode active material" or a "negative electrode active material", and is particularly used as a "negative electrode active material".

[0016] The electrode mix of the present disclosure includes silicon clathrate particles and amorphous silicon particles.

[0017] In this disclosure, "silicon clathrate particles" means silicon particles having a silicon clathrate content of more than 50 mass%, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, 95 mass% or more, or 99 mass% or more.

[0018] In the present disclosure, "amorphous silicon particles" means silicon particles having an amorphous silicon content of more than 50% by mass, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or 99% by mass or more.

[0019] The electrode mixture of the present disclosure satisfies the following relationship: 0atom%<number of silicon atoms in an amorphous silicon particle / (number of silicon atoms in an amorphous silicon particle + number of silicon atoms in a silicon clathrate particle)<50atom%.

[0020] The number of silicon atoms in an amorphous silicon particle / (number of silicon atoms in an amorphous silicon particle+number of silicon atoms in a silicon clathrate particle) may be 1 atom% or more, 2 atom% or more, 3 atom% or more, 4 atom% or more, 5 atom% or more, or 8 atom% or more, and may be 40 atom% or less, 30 atom% or less, 25 atom% or less, 20 atom% or less, 15 atom% or less, or 12 atom% or less, or may be 10 atom%.

[0021] The method for quantifying the silicon clathrate particles and amorphous silicon particles in the electrode mixture includes a method using a scanning electron microscope (SEM) and electron backscatter diffraction (EBSD). More specifically, the following method can be used for quantification. That is, first, the electrode mixture is embedded in a resin, and the resin is cut together to obtain a cross section. Then, the obtained cross section is subjected to EBSD measurement at a magnification that includes, for example, about 5 particles of the electrode mixture. Furthermore, the obtained diffraction pattern is analyzed, and a mapping image is obtained by IPF (Inverse Pole Figure) mapping. This allows the silicon clathrate particles and amorphous silicon particles in the electrode mixture to be quantified. The EBSD measurement is a type of crystal analysis using a SEM (scanning electron microscope), and the following measurement conditions can be adopted. Section preparation Equipment: JEOL SM-09010 cross-section polisher, ion source: argon, acceleration voltage: 5.5 kV ·SEM Equipment: JEOL JSM-7000F field emission scanning electron microscope, accelerating voltage: 7.5 kV EBSD Equipment: TSL OIM crystal orientation analyzer, accelerating voltage: 15 kV In addition to the above conditions, the cross section may be prepared under the following conditions: apparatus: Hitachi High-Technologies IM-4000, ion source: Ar, acceleration voltage: 5.0 kV.

[0022] The ionic conductivity of the particles in the electrode mix may be 0.0655 mS / cm or more, 0.0660 mS / cm or more, 0.0665 mS / cm or more, 0.0670 mS / cm or more, 0.0675 mS / cm or more, or 0.0680 mS / cm or more, and may be 0.0682 mS / cm or less, or 0.0681 mS / cm or less.

[0023] This ionic conductivity can be measured by the following method. That is, first, a confining pressure is applied to a pellet obtained by pressing the electrode mixture. Then, the obtained sample is calculated by an AC impedance method while being kept at 25°C. For the measurement, a Solartron 1260 manufactured by Solartron Analytical can be used. The measurement conditions can be an applied voltage of 5 mV and a measurement frequency range of 0.01 to 1 MHz.

[0024] <Silicon clathrate particles> Silicon clathrate particles can be prepared by preparing a sodium silicon (NaSi) alloy and removing sodium from the NaSi alloy.

[0025] Specifically, a silicon source is reacted with a sodium source such as sodium hydride to prepare a NaSi alloy. The NaSi alloy thus prepared is then heated to remove sodium from the NaSi alloy and form a clathrate, thereby preparing silicon clathrate particles. Alternatively, the NaSi alloy thus prepared is reacted with aluminum fluoride as a sodium trapping agent to remove sodium from the NaSi alloy and form a clathrate, thereby preparing silicon clathrate particles.

[0026] The silicon clathrate particles may be porous silicon clathrate particles. The porous silicon clathrate can absorb expansion due to charging and discharging by its voids.

[0027] Examples of methods for producing porous silicon clathrate particles include, but are not limited to, methods including mixing silicon with metallic lithium to obtain a lithium silicon (LiSi) alloy, reacting the obtained LiSi alloy with ethanol to obtain porous silicon, and using the obtained porous silicon as a silicon raw material to obtain silicon clathrate particles as described above.

[0028] <Amorphous silicon particles> The method for producing amorphous silicon particles includes, but is not limited to, a method including mixing silicon with metallic lithium to obtain a lithium silicon (LiSi) alloy, and reacting the obtained LiSi alloy with ethanol. This method can obtain porous amorphous silicon particles.

[0029] The electrode mixture of the present disclosure optionally contains a solid electrolyte, a conductive additive, and a binder.

[0030] <Solid electrolyte> The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for use in lithium ion batteries can be used. For example, the solid electrolyte may be a sulfide solid electrolyte.

[0031] Examples of sulfide solid electrolytes include, but are not limited to, sulfide amorphous solid electrolytes, sulfide crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2 (Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Clx etc.; or combinations thereof, but are not limited to these.

[0032] The sulfide solid electrolyte may be a glass or a crystallized glass (glass ceramic).

[0033] <Conductive assistant> The conductive assistant is not particularly limited. For example, the conductive assistant may be VGCF (Vapor Grown Carbon Fiber), acetylene black (AB), Ketjen Black (KB), carbon nanotube (CNT), carbon nanofiber (CNF), etc., but is not limited thereto.

[0034] <binder> The binder is not particularly limited. For example, the binder may be a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), or styrene butadiene rubber (SBR), or a combination thereof, but is not limited thereto.

[0035] Lithium-ion battery The lithium ion battery of the present disclosure may be a liquid battery or a solid-state battery. In the present disclosure, a "solid-state battery" refers to a battery that uses at least a solid electrolyte as an electrolyte, and therefore a solid-state battery may use a combination of a solid electrolyte and a liquid electrolyte as an electrolyte. The solid-state battery of the present disclosure may also be an all-solid-state battery, i.e., a battery that uses only a solid electrolyte as an electrolyte.

[0036] The lithium ion battery of the present disclosure can be restrained from both sides of the stacking direction of each of the layers by restraining members such as end plates. Examples of the restraining method include, but are not limited to, a method that utilizes the restraining torque of a bolt.

[0037] The lithium ion battery of the present disclosure has an electrode active material layer, and the electrode active material layer contains the electrode mixture of the present disclosure. In particular, the lithium ion battery of the present disclosure may have a negative electrode mixture as the electrode mixture of the present disclosure, and in this case, may include a negative electrode current collector layer, a negative electrode active material layer containing the electrode mixture of the present disclosure, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order. Below, the layers constituting the lithium ion battery when the negative electrode mixture is the electrode mixture of the present disclosure will be described.

[0038] <Negative electrode current collector layer> The material used for the negative electrode current collector layer is not particularly limited, and any material that can be used as a negative electrode current collector for a battery can be appropriately adopted. For example, the material may be copper, a copper alloy, or copper plated or vapor-deposited with nickel, chromium, carbon, or the like, but is not limited to these.

[0039] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0040] <Negative electrode active material layer> The negative electrode active material layer contains the electrode mixture of the present disclosure. For the electrode mixture, reference can be made to the above description of the electrode mixture of the present disclosure.

[0041] When the negative electrode active material layer contains a solid electrolyte, the mass ratio of the electrode active material particles to the solid electrolyte in the negative electrode active material layer (mass of electrode active material particles:mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 40:60.

[0042] The negative electrode active material layer may have a thickness of, for example, 0.1 to 1000 μm.

[0043] <Solid electrolyte layer> The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the solid electrolyte and the binder, the above description regarding the electrode mixture of the present disclosure can be referred to.

[0044] The thickness of the solid electrolyte layer is, for example, 0.1 to 300 μm, and preferably 0.1 to 100 μm.

[0045] <Cathode active material layer> The positive electrode active material layer is a layer containing a positive electrode active material, and optionally a solid electrolyte, a conductive assistant, a binder, a thickener, and the like.

[0046] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y Li-Mn spinel substituted with different elements, which has a composition represented by MyO4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn), and lithium titanate (Li x TiO y ), lithium metal phosphate (LiMPO4, M is one or more metals selected from Fe, Mn, Co, and Ni), and the like, but are not limited thereto.

[0047] The positive electrode active material may have a coating layer. The coating layer is a layer containing a substance that has lithium ion conductivity, is low in reactivity with the positive electrode active material and the solid electrolyte, and can maintain the shape of the coating layer without flowing even when it comes into contact with the active material and the solid electrolyte. Specific examples of materials constituting the coating layer include LiNbO3, Li4Ti5O 12 , Li3PO4, etc., but are not limited to these.

[0048] The shape of the positive electrode active material may be, for example, particulate. The average particle size (D50) of the positive electrode active material is not particularly limited, but may be, for example, 10 nm or more, and may be 100 nm or more. On the other hand, the average particle size (D50) of the positive electrode active material is, for example, 50 μm or less, and may be 20 μm or less. The average particle size (D50) can be calculated, for example, from measurements using a laser diffraction particle size distribution meter or a scanning electron microscope (SEM).

[0049] For the solid electrolyte, the conductive assistant, and the binder, reference can be made to the above descriptions regarding the electrode mixture of the present disclosure.

[0050] When the positive electrode active material layer contains a solid electrolyte, the mass ratio of the positive electrode active material to the solid electrolyte in the positive electrode active material layer (mass of positive electrode active material: mass of solid electrolyte) is preferably 85:15 to 30:70, and more preferably 80:20 to 50:50.

[0051] The thickness of the positive electrode active material layer is, for example, 0.1 μm to 1000 μm, preferably 1 μm to 100 μm, and more preferably 30 μm to 100 μm.

[0052] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used as a positive electrode current collector for a battery can be appropriately adopted. For example, SUS, nickel, chromium, gold, platinum, aluminum, iron, titanium, zinc, etc., and these metals plated or vapor-deposited with nickel, chromium, carbon, etc. may be used, but is not limited to these.

[0053] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0054] <<How lithium-ion batteries are manufactured>> The disclosed method of manufacturing a lithium ion battery includes forming an electrode active material layer, and the electrode active material layer contains the disclosed electrode mix.

[0055] An example of a method for forming an electrode active material layer includes providing an electrode mixture slurry containing the electrode mixture and a dispersion medium of the present disclosure, applying the electrode mixture slurry to a substrate, and drying and removing the dispersion medium to form an electrode active material layer.

[0056] A method of forming a battery, for example when the negative electrode active material layer contains the electrode mixture of the present disclosure, may include, in addition to forming a negative electrode active material layer containing the electrode mixture, arranging a negative electrode current collector layer, a negative electrode active material layer, an electrolyte layer, a positive electrode active material layer, and a positive electrode current collector layer in this order. EXAMPLES

[0057] Synthesis Example 1 Synthesis of silicon clathrate particles (alloying) A sodium silicon (NaSi) alloy was produced using Si powder (Kojundo Kagaku, SIEPB32) and sodium hydride (NaH) as a sodium (Na) source. The NaH used was washed with hexane in advance. NaH and Si powder were weighed out so that the molar ratio was 1.05:1, and the weighed NaH and Si powder were mixed in a cutter mill. The resulting mixture was heated in a heating furnace under an argon atmosphere at 700°C for 20 hours to obtain a powdered NaSi alloy.

[0058] (Clatification) The obtained NaSi alloy was heated at 340°C in an argon atmosphere in a heating furnace and then pulverized in a ball mill (manufactured by Fritsch) to obtain silicon clathrate particles. Note that the surface of the silicon clathrate particles may contain a coating or impurities containing O, C, or N elements.

[0059] Synthesis Example 2 Synthesis of amorphous silicon particles Metallic lithium (Li) and Si powder were weighed out to a molar ratio of 4:1, and were reacted by mixing in a mortar under argon atmosphere at room temperature for 0.5 hours. This resulted in Li4Si. The Li4Si obtained was reacted with ethanol under argon atmosphere. This reaction product was filtered, and the filtered solid was dried at 120°C for 3 hours or more to obtain powdered porous silicon. The porous silicon was washed with a 3 wt% hydrogen fluoride (HF) solution, filtered, and then dried at 120°C for 3 hours or more to obtain amorphous silicon particles.

[0060] Comparative Example 1 (Making a lithium-ion battery) (Preparation of negative electrode mixture) Butyl butyrate, a 5 wt% butyl butyrate solution of polyvinylidene fluoride (PVDF) binder, vapor grown carbon fiber (VGCF) as a conductive assistant, silicon clathrate particles of Synthesis Example 1, and Li2S-P2S5 glass ceramic as a sulfide solid electrolyte were added to a polypropylene container, and the mixture was stirred for 30 seconds with an ultrasonic dispersing device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.) to obtain a slurry-like negative electrode mixture (negative electrode mixture slurry).

[0061] (Formation of negative electrode active material layer) The obtained negative electrode composite slurry was applied onto a copper (Cu) foil serving as a negative electrode current collector layer by the blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C to form a negative electrode active material layer on the negative electrode current collector layer.

[0062] (Formation of solid electrolyte layer) Heptane, a 5 wt% heptane solution of butylene rubber (BR)-based binder, and Li2SP2S5-based glass ceramic as a sulfide solid electrolyte were added to a polypropylene container and stirred for 30 seconds with an ultrasonic disperser (UH-50, manufactured by SMT Co., Ltd.). Next, the container was shaken for 30 minutes with a shaker (TTM-1, manufactured by Shibata Scientific Co., Ltd.) to obtain a solid electrolyte slurry.

[0063] The obtained solid electrolyte slurry was applied onto an aluminum (Al) foil as a release sheet by a blade method using an applicator, and dried for 30 minutes on a hot plate heated to 100°C to form a solid electrolyte layer. Multiple solid electrolyte layers were produced.

[0064] (Preparation of Positive Electrode Mixture) A polypropylene container is filled with butyl butyrate, a 5 wt% butyl butyrate solution of a PVDF-based binder, and LiNi with an average particle size of 6 μm as the positive electrode active material. 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li2S-P2S5-based glass ceramic as a sulfide solid electrolyte, and VGCF as a conductive additive were added to the container and stirred for 30 seconds with an ultrasonic dispersion device (UH-50 manufactured by SMT Co., Ltd.). Next, the container was shaken for 3 minutes with a shaker (TTM-1 manufactured by Shibata Scientific Co., Ltd.), further stirred for 30 seconds with the ultrasonic dispersion device, and shaken for 3 minutes with the shaker to obtain a slurry-like positive electrode mixture (positive electrode mixture slurry).

[0065] (Formation of Positive Electrode Active Material Layer) The obtained positive electrode mixture slurry was applied onto an Al foil serving as a positive electrode current collector layer by a blade method using an applicator, and then dried for 30 minutes on a hot plate heated to 100°C, thereby forming a positive electrode active material layer on the positive electrode current collector layer.

[0066] (Battery Assembly) The positive electrode current collector layer, the positive electrode active material layer, and the first solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 100 kN / cm and a temperature of 165° C. to obtain a positive electrode laminate.

[0067] The negative electrode current collector layer, the negative electrode active material layer, and the second solid electrolyte layer were laminated in this order, and the laminate was set in a roll press and pressed at a pressure of 60 kN / cm and a temperature of 25° C. to obtain a negative electrode laminate.

[0068] Furthermore, the Al foil as a release sheet was peeled off from the surfaces of the solid electrolyte layers of the positive electrode laminate and the negative electrode laminate, and then the Al foil as a release sheet was peeled off from the third solid electrolyte layer.

[0069] The positive electrode laminate and the negative electrode laminate were laminated on top of each other so that the solid electrolyte layer side of each laminate faced the third solid electrolyte layer, and the laminate was set in a flat uniaxial press and pre-pressed at 100 MPa and 25° C. for 10 seconds, and finally the laminate was set in a flat uniaxial press and pressed for 1 minute at a pressing pressure of 200 MPa and a pressing temperature of 120° C. In this way, the all-solid-state battery of Comparative Example 1 was obtained.

[0070] Comparative Examples 2 to 4 and Examples 1 to 3 In preparing the negative electrode composite, the silicon clathrate particles of Synthesis Example 1 and the amorphous silicon particles of Synthesis Example 2 were used in the ratio of the number of silicon atoms shown in Table 1. The same procedure as in Comparative Example 1 was used to obtain the all-solid-state batteries of Comparative Examples 2 to 4 and Examples 1 to 3.

[0071] "evaluation" Quantitative Analysis of Silicon Particles in Electrode Mixture The silicon clathrate particles and amorphous silicon particles in the electrode composite were quantified using a scanning electron microscope (SEM) and electron backscatter diffraction (EBSD). More specifically, the quantification was performed using the following method. That is, first, the electrode composite was embedded in resin and cut together with the resin to obtain a cross section. Then, EBSD measurement was performed on the obtained cross section at a magnification that included about 5 particles of the electrode composite. Furthermore, the obtained diffraction pattern was analyzed, and a mapping image was obtained by IPF (Inverse Pole Figure) mapping. In this way, the silicon clathrate particles and amorphous silicon particles in the electrode composite were quantified. The following measurement conditions were adopted. Section preparation Equipment: JEOL SM-09010 cross-section polisher, ion source: argon, acceleration voltage: 5.5 kV ·SEM Equipment: JEOL JSM-7000F field emission scanning electron microscope, accelerating voltage: 7.5 kV EBSD Equipment: TSL OIM crystal orientation analyzer, accelerating voltage: 15 kV

[0072] <Measurement of ionic conductivity> The ionic conductivity of the particles in the electrode mixture was measured by the following method. That is, first, a confining pressure was applied to a pellet obtained by pressing the electrode active material particles. Then, the obtained sample was kept at 25°C and calculated by an AC impedance method. For the measurement, a Solartron 1260 from Solartron Analytical was used. The measurement conditions were an applied voltage of 5 mV and a measurement frequency range of 0.01 to 1 MHz.

[0073] <Measurement of increase in confining pressure> The cell prepared using the restraining tool was restrained at a predetermined restraining pressure, and the increase in restraining pressure was measured when the cell was charged at a constant current and constant voltage up to 4.55 V at a 10-hour rate (1 / 10C). A large increase in the restraining pressure means that the active material has a large expansion amount. The increase in the restraining pressure is the difference between the maximum and minimum values ​​of the restraining pressure, and the values ​​of the examples are shown as relative values ​​when the value of Comparative Example 1 is set to 100.

[0074] "result" Table 1 shows the measurement results of the ratio of silicon atoms in each silicon particle, the ionic conductivity of the particles in the electrode mixture, and the increase in the confining pressure of the battery.

[0075] [Table 1]

[0076] As shown in Table 1, the battery of the example containing the electrode mixture of the present disclosure had a smaller increase in confining pressure than the battery of the comparative example. This is believed to be because the electrode mixture of the present disclosure contains silicon clathrate particles that have a high expansion coefficient suppression effect, and contains amorphous silicon particles within the range of the present disclosure, thereby increasing the ion conductivity.

Claims

1. An electrode mixture comprising silicon clathrate particles and amorphous silicon particles, and satisfying the following relational formula: 0 atom %<number of silicon atoms in the amorphous silicon particle / (number of silicon atoms in the amorphous silicon particle+number of silicon atoms in the silicon clathrate particle)<50 atom %.

2. The electrode mixture according to claim 1, which satisfies the following relational formula: 0 atom %<number of silicon atoms in the amorphous silicon particle / (number of silicon atoms in the amorphous silicon particle+number of silicon atoms in the silicon clathrate particle)≦30 atom %.

3. The electrode mix of claim 1 , wherein the amorphous silicon particles are porous amorphous silicon particles.

4. An electrode active material layer is provided, and The electrode active material layer contains the electrode mixture according to any one of claims 1 to 3. Lithium-ion battery.

5. forming an electrode active material layer; and The electrode active material layer contains the electrode mixture according to any one of claims 1 to 3. How lithium-ion batteries are manufactured.

6. 6. The method of claim 5, comprising forming the electrode active material layer by a method comprising the steps of: Providing an electrode mixture slurry containing the electrode mixture according to any one of claims 1 to 3 and a dispersion medium; and The electrode mixture slurry is applied to a substrate, and the dispersion medium is then dried to form the electrode active material layer.

Citation Information

Patent Citations

  • Active material, negative electrode layer, battery and these manufacturing methods

    JP2021158003A